2016
DOI: 10.3389/fpsyg.2015.01903
|View full text |Cite
|
Sign up to set email alerts
|

Of Huge Mice and Tiny Elephants: Exploring the Relationship Between Inhibitory Processes and Preschool Math Skills

Abstract: The cognitive mechanisms underpinning the well-established relationship between inhibitory control and early maths skills remain unclear. We hypothesized that a specific aspect of inhibitory control drives its association with distinct math skills in very young children: the ability to ignore stimulus dimensions that are in conflict with task-relevant representations. We used an Animal Size Stroop task in which 3- to 6-year-olds were required to ignore the physical size of animal pictures to compare their real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 59 publications
4
27
0
Order By: Relevance
“…For example, Dark and Benbow (Dark & Benbow, 1994) found that working memory tasks with numerical stimuli were more closely related to mathematical precocity than non-numerical stimuli across a range of tasks in adults. Similarly, studies of children have demonstrated that inhibitory control and working memory of numerical information accounts for significant variance in individual differences in mathematics ability and early numeracy beyond similar non-numerical measures of executive function (Bull & Scerif, 2001;Merkley, Thompson, & Scerif, 2016).…”
Section: Full Range Of Achievementmentioning
confidence: 99%
“…For example, Dark and Benbow (Dark & Benbow, 1994) found that working memory tasks with numerical stimuli were more closely related to mathematical precocity than non-numerical stimuli across a range of tasks in adults. Similarly, studies of children have demonstrated that inhibitory control and working memory of numerical information accounts for significant variance in individual differences in mathematics ability and early numeracy beyond similar non-numerical measures of executive function (Bull & Scerif, 2001;Merkley, Thompson, & Scerif, 2016).…”
Section: Full Range Of Achievementmentioning
confidence: 99%
“…Most previous research exploring the cognitive processes behind science and maths misconceptions has been performed on children [ 12 , 16 , 19 21 ] or adults [ 13 , 14 , 17 ]. The current study investigated the role of inhibitory control in counterintuitive reasoning, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there are many studies claiming that gender-based differentiation in different math skills did not occur significantly in the pre-school period and begins after 7-8 years of age (Williams, White & MacDonald, 2016;Merkley, Thompson & Scerif, 2016;Purpura, Reid, Eiland & Baroody, 2015) The effect of age-related development in assessing the probabilistic reasoning is also seen in this study -as in many different types of research (Gonzalez & Girotto, 2011;Ergül, 2014;Liu & Chou, 2015). Even the youngest children in the study group were found to have intuitive probability considerations, but the correct response rates of older children were found to be higher.…”
Section: Conclusion and Discussionmentioning
confidence: 99%